2016
DOI: 10.1186/s12891-016-0923-0
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of topical tranexamic acid in total hip arthroplasty: a meta-analysis

Abstract: AbstractsBackgroundTopical tranexamic acid (TXA) has been shown to be effective in reducing blood loss and the need for transfusion after total knee arthroplasty. However, the effectiveness of topical TXA use in total hip arthroplasty (THA) still remains unclear. The purpose of this meta-analysis is to examine the safety and efficacy of topical use of TXA following THA.Hypothesis: Topical TXA reduces blood loss and transfusion rates without increasing risk of deep vein thrombosis in patients with THA.MethodsAn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 27 publications
(45 reference statements)
0
39
0
3
Order By: Relevance
“…A lack of systemic absorption with topical TXA is one suggested reason for such an effect. Comparable results have previously been identified with topical TXA in hip and knee arthroplasty . Caution should exercised, however, when considering use in hemiarthroplasty, as recent research has identified a potential cytotoxic effect on chondrocytes in an animal model .…”
Section: Discussionmentioning
confidence: 86%
“…A lack of systemic absorption with topical TXA is one suggested reason for such an effect. Comparable results have previously been identified with topical TXA in hip and knee arthroplasty . Caution should exercised, however, when considering use in hemiarthroplasty, as recent research has identified a potential cytotoxic effect on chondrocytes in an animal model .…”
Section: Discussionmentioning
confidence: 86%
“…In THA and TKA, the most notable complication reported in the literature is venous thromboembolism. The vast majority of orthopaedic TXA studies show no increase in the rate of venous thromboembolism events [29][30][31]43,44]. Nishihara, et al is the only study in the recently published literature known to the authors that demonstrated a significant increase in venous thromboembolic events after TXA administration in total joint arthroplasty [18].…”
Section: Oral Usementioning
confidence: 99%
“…The most common metrics include total blood loss, intra-operative blood loss, post operative blood loss, drain output, hemoglobin reduction, and transfusion rates. Meta analyses comparing studies that use the same metrics for efficacy have widely determined TXA use is superior to placebo controls, however such analyses are rarely, if ever, able to compare studies using the exact same dosing regimens and so their conclusions are typically broadly applicable to the use of TXA but do not delve into the optimal IV and or topical dosing strategies other than speculation [6,7,[29][30][31].…”
Section: And Topical Usementioning
confidence: 99%
“…Evangelista et al [31] reported an elevated risk of deep vein thrombosis and pulmonary embolism after application of TXA. However, several meta-analyses showed TXA might not increase thromboembolic events in patients undergoing THA and the incidence of thromboembolic events was very low [30,[32][33][34][35]. Lucas-Polomeni et al [36] reported drug allergy with anaphylactic shock after intravenous TXA.…”
Section: Discussionmentioning
confidence: 99%